Mobbing on University Staff: a Systematic Review - Rojas-Solís, José Luis (2019)
A great variety of studies on workplace harassment has been approached by different working groups because they show organizational and individual conditions that facilitate the development of this problem; for that reason the present study carries out a systematic review of scientific research on mobbing on university staff, using the following databases as a collection tool: La Referencia, EBSCO, Web of Science, Scielo and SCOPUS. The study included research published in the period between the years2000 and 2019. The approach of the studies analyzed was quantitative and mixed, with a non-experimental and cross-sectional design, and a correlational and descriptive scope. With respect to the instruments used, the importance of theoretical updating and validation is highlighted, as well as the need to implement and create new instruments to measure this phenomenon. In the same way, research about mobbing on university staff in the workplace is encouraged, considering the analysis of sex differences and harassment behaviors.